The journalist's predicament difficult choices in a declining profession - Powers, Matthew 1980- (Columbia University Press, 2023)
"Low pay. Uncertain work prospects. Diminished prestige. Why would anyone still want be a journalist? Drawing on in-depth interviews in France and the United States, Matthew Powers and Sandra Vera-Zambrano explore the ways individuals come to believe that journalism is a worthy pursuit-and how that conviction is managed and sometimes dissolves amid the profession's ongoing upheavals. For many people, journalism represents a job that is interesting and substantial, with opportunities for expression, a sense of self-fulfillment, and a connection to broader social values. By distilling complex ideas, holding the powerful to account, and revealing hidden realities, journalists play a crucial role in helping audiences make sense of the world. Experiences in the profession, though, are often far more disappointing. Many find themselves doing tasks that bear little relation to what attracted them initially or are frustrated by institutions privileging what sells over what informs. The imbalance between the profession's economic woes and its social importance threatens to erode individuals' beliefs that journalism remains a worthwhile pursuit. Powers and Vera-Zambrano emphasize that, as with many seemingly individual choices, social factors-class, gender, education, and race-shape how journalists make sense of their profession and whether or not they remain in it. An in-depth story of one profession under pressure, The Journalist's Predicament uncovers tensions that also confront other socially important jobs like teaching, nursing, and caretaking"--
Keywords: Stress; Beruf; Journalist; Journalism; Journalists / Attitudes; Journalists / Job stress